An evaluation on musharakah mutanaqisah based house financing by islamic banks in Malaysia - Siti Fariha Muhamad; Azira Hanani Ab. Rahman (2013)
Musharakah Mutanaqisah has been suggested as a better alternative of Islamic financing contract to replace the controversial Bay Bithaman Ajil contract in the house financing. However, to date, only a few Islamic financial instituitions in Malaysia has implemented Musharakah Mutanaqisah as a housing financing tool to replace the Bay Bithaman Ajil, a Murabahah based contract, along with a few others still make both contracts available to provide the variety to the customers. Musharakah Mutanaqisah is said to be an ideal contract that is more Shariah compliant, free from the element of riba’, gharar and maysir and is asserted to abolish the major problems exist in the Bay Bithaman Ajil contract. However this statement never been tested. The purpose of this paper is to provide some insights and evaluation on this issue by examining the conformity of implementation of Musharakah Mutanaqisah in the housing financing by the Islamic financial institutions in Malaysia against the Shariah tenets and rules. The evaluation presents some problems, issues and challenges evolves in its implementation and the possibility of more effective implementation of Musharakah Mutanaqisah to replace Bay Bithaman Ajil based house financing contract.